2011
DOI: 10.1371/journal.pone.0024584
|View full text |Cite
|
Sign up to set email alerts
|

MiR-34a Targeting of Notch Ligand Delta-Like 1 Impairs CD15+/CD133+ Tumor-Propagating Cells and Supports Neural Differentiation in Medulloblastoma

Abstract: BackgroundThrough negative regulation of gene expression, microRNAs (miRNAs) can function as oncosuppressors in cancers, and can themselves show altered expression in various tumor types. Here, we have investigated medulloblastoma tumors (MBs), which arise from an early impairment of developmental processes in the cerebellum, where Notch signaling is involved in many of the cell-fate-determining stages. Notch regulates a subset of MB cells that have stem-cell-like properties and can promote tumor growth. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 44 publications
6
100
1
Order By: Relevance
“…Down-regulation of Dll1 expression by miR-34a negatively regulates cell proliferation, and induces apoptosis and neural differentiation in MB cells. Infection of adenoviruses carrying the precursor miR-34a induces neurogenesis of tumor spheres and reduces tumor burden in cerebellum xenografts of athymic mice, demonstrating an anti-tumorigenic role of miR-34a in vivo [52]. Interestingly, miR-34a is able to confer chemosensitivity as well through directly targeting the 3' UTRs of MAGE-A genes, reducing MAGE-A and increasing p53 in MB [54].…”
Section: Microrna (Mirna) -Based Gene Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…Down-regulation of Dll1 expression by miR-34a negatively regulates cell proliferation, and induces apoptosis and neural differentiation in MB cells. Infection of adenoviruses carrying the precursor miR-34a induces neurogenesis of tumor spheres and reduces tumor burden in cerebellum xenografts of athymic mice, demonstrating an anti-tumorigenic role of miR-34a in vivo [52]. Interestingly, miR-34a is able to confer chemosensitivity as well through directly targeting the 3' UTRs of MAGE-A genes, reducing MAGE-A and increasing p53 in MB [54].…”
Section: Microrna (Mirna) -Based Gene Therapymentioning
confidence: 98%
“…miRNAs-mediated inhibition of MB cell proliferation and MB metastasis by targeting the Notch signaling pathway have been tested in xenograft model. Since the Notch signaling pathway regulates a subset of MB cells to enhance the stem-cell-like properties and promotes tumor growth, miRNAs such as miR199b-5p and miR34a that target the Notch signaling pathway may be engineered for MB therapy [48,52]. It has been shown that miR199b-5p level is significantly higher in non-metastatic MB cases than in metastatic cases, suggesting miR199b-5p conferred inhibition of MB metastasis.…”
Section: Microrna (Mirna) -Based Gene Therapymentioning
confidence: 99%
“…The miR-34a has further been demonstrated to target Notch signaling in glioblastoma and medulloblastoma stem cells by directly regulating the Notch-1 and Notch-2 pathway components. The miR-34a expression in glioblastoma cells significantly reduced in vivo xenograft growth and inhibits the tumor propagating ability of medulloblastoma cells [58,59].…”
Section: Notch Signalingmentioning
confidence: 98%
“…MiRNA 199b-5p was found downregulated in MB patients' tissues compared to healthy control cerebellum tissues. The analysis of 61 patients with MB showed that the expression of miR-199b-5p in the nonmetastatic cases was Targets Notch ligand Delta-like 1(Dll1), impairment of cancer stem cell compartments [ 111 ] signifi cantly higher than in the metastatic cases. The correlation with survival for the patients with high levels of miR-199b expression showed a positive trend to better overall survival than for the low-expressing patients.…”
Section: Profi Ling Mb Transcriptomementioning
confidence: 99%